Affinity Chromatography of RNA-Dependent DNA Polymerase from RNA Tumor Viruses on a Solid Phase Immunoadsorbent - Livingston, David M. (1972)
A solid phase immunoadsorbent specific for RNA-dependent DNA polymerase from murine and feline RNA tumor viruses has been prepared. The enzymes from murine and feline virus but not from avian virus bind to columns of this material. Bound enzymes can be eluted in active form. This method has permitted selective purification of viral enzyme from crude extracts of virus-transformed cells, since the immunoadsorbent has no affinity for cellular DNA polymerases.